Enhanced fee-for-service model and access to physician services: Evidence from Family Health Groups in Ontario - Jasmin Kantarevic; Boris Kralj; Darrel Weinkauf (Institute for the Study of Labor (IZA), 2010)
We study an enhanced fee-for-service model for primary care physicians in the Family Health Groups (FHG) in Ontario, Canada. In contrast to the traditional fee-for-service (FFS) model, the FHG model includes targeted fee increases, extended hours, performance-based initiatives, and patient enrolment. Using a long panel of claims data, we find that the FHG model significantly increases physician productivity relative to the FFS model, as measured by the number of services, patient visits, and distinct patients seen. We also find that the FHG physicians have lower referral rates and treat slightly more complex patients than the comparable FFS physicians. These results suggest that the FHG model offers a promising alternative to the FFS model for improving access to physician services.
Keywords: I10; I12; I18; 330; Access to physician services; physician productivity; remuneration; primary care; Family Health Groups; Ontario; Canada; Basisgesundheitsversorgung; Ärzte; Vergütungssystem; Gesundheitsversorgung; Ontario (Provinz)